Perancangan UI/UX Layanan Jahit Pakaian Dengan Menggunakan Pendekatan Design Thinking di Kota Malang - Lefteuw, Everista Richarda; Ramadhan, Viry Puspaning (J-INTECH (Journal of Information and Technology), 2024)
The development of technology greatly affects the needs of life and the way people think, especially the development of technology software. This then makes the development of User Interface (UI) and User Experience (UX) need to be a concern. Currently, the number of tailors in Malang City is increasing and has different specialties, and consumer demand is also increasing so that to get a sewing place, customers must take the time and come directly to the tailor. The problem is, not everyone can find out all the locations of sewing places around his house and whether the sewing place can still accept customers or not. This research aims to design a prototype application of clothing sewing services in Malang City and to provide information on clothing sewing services that can meet the needs of the community. Researchers use the Application of Design Thinking because it is able to produce more innovative and effective solutions in designing products or services and use the figma application to design prototypes. The testing process is carried out online using Maze Design as a test on interface design and System Usability Scale (SUS) which aims to measure user perceptions of interface usability. The test results using SUS (system usability scale) obtained an average value of 71.38, so it can be concluded that the system is well received.